(untitled) (Bangladesh Journal of Public Administration, 2021)
Antibiotic resistance has become a serious concern for ensuring quality health care in upcoming decade. The main objective of the study was to identify some influential determinants of knowledge, attitude and practice about antibiotic usage of rural people specially focusing on the gender perspective. A cross sectional study design and quantitative approach was followed to conduct the study. Result shows that the knowledge, attitude and practice scores on antibiotic usage are below average. Specially rural women are significantly lagging behind than their male counterparts. Due to absence of doctors and poor financial condition of the villagers, they frequently take antibiotics to speedup their recobvery process without fulfilling the required dosage. Immediate policy measures should be taken by the government to accommodate more doctors in the rural area, raise awareness on antibiotic resistance and shut down the illegal drugshops.